Differences in Comorbidities and Clinical Burden of Severe Bronchopulmonary Dysplasia Based on Disease Severity - Hye-Rim Kim; Hye-Rim Kim; Young Hwa Jung; Young Hwa Jung; Beyong Il Kim; Beyong Il Kim; So Young Kim; Chang Won Choi; Chang Won Choi (Frontiers Media S.A., 2021)
Background: The present study compared baseline characteristics, comorbidities and clinical burden of pre-term infants with type 1 and 2 severe bronchopulmonary dysplasia (BPD) Collaborative classification.Methods: This study was a prospective cohort study of pre-term (<32 weeks) very-low-birth-weight infants. Severe BPD was divided into type 1 severe BPD requiring of ≥30% oxygen and/or non-invasive ventilation at 36 weeks post-menstrual age (PMA), and type 2 severe BPD requiring invasive mechanical ventilation at 36 weeks PMA. Baseline characteristics, comorbidities, and clinical burden were compared between these two types of severe BPD.Results: Of the 1,328 infants included, 983 (74.0%) developed type 1 severe BPD, and 345 (26.0%) developed type 2 severe BPD. Lower birth weight, small for gestational age, lesser maternal pre-mature rupture of membrane, lower 5-min Apgar score, air leak, pulmonary hemorrhage, surgical ligation of patent ductus arteriosus, necrotizing enterocolitis, and late-onset sepsis were significantly associated with type 2 severe BPD. Compared with infants with type 1 severe BPD, infants with type 2 severe BPD had an increased risk of mortality (aOR 18.64, 95% CI 10.81-32.13), pulmonary hypertension (aOR 2.16, 95% CI 1.59-2.93), and tracheostomy (aOR 10.38, 95% CI 2.05-52.49).Conclusions: Our data highlight the substantially greater mortality and clinical burden in infants with type 2 severe BPD than infants with type 1 severe BPD. A comprehensive and multidisciplinary approach is needed for infants with type 2 severe BPD.